Readiness of nurses when faced with a patient’s death - Kowalenko, Marta; Krajewska-Kułak, Elżbieta; Kowalewska, Beata; Kułak-Bejda, Agnieszka; Kulik, Teresa; Gaworska-Krzemińska, Aleksandra; Van Damme-Ostapowicz, Katarzyna (Frontiers in Public Health, 2024)
The death of a patient negatively affects the professional dimension of nurses' functioning and also their private lives, where professional experiences and emotions are often transmitted.The main aim of the study was to discover how the nursing staff assessed their self-efficacy in dealing with the death of a patient.The researchers used a diagnostic survey method and a self-authored survey, SWLS -Life Satisfaction Scale), CISS (Coping Inventory for Stressful Situations), GSES (Generalised Self-Efficacy Scale, CECS (Courtauld Emotional Control Scale), The Death Anxiety and Fascination Scale with the Death Anxiety Subscale. The study group consisted of 287 individuals.Working in a hospital is stressful in the opinion of 79.44% of the respondents. 39.37% of the respondents feared death. In the course of work, the death of a patient in the department was sometimes experienced by 34.84% of the respondents, always experienced by 29.97%. The respondents usually did not make their compassion for a dying patient based on the patient's position in society (57.84%). In the case of the majority (84.67%) of the respondents, the employer did not provide mental support for the staff in difficult situations. The majority of the respondents did not feel the need to broaden their knowledge of death and dying (64.11%).The surveyed nurses most often presented low or average life satisfaction, high self-efficacy, average levels of stress and coping in all three styles (with a preference for avoidance-oriented), and a high level of death fascination and an average level of death anxiety.The majority of the nurses in difficult situations and when a stressful situation occurred did not receive support from their employer or from physicians, but could count on the assistance of fellow nurses and a divisional nurse. The majority of the respondents felt that psychological support in their work was important and would gladly benefit from it. Although most nurses did not feel the need to broaden their knowledge of death/dying, they would take part in such a course if it were possible.